The Effectiveness of SEFT Complementary Therapy (Spiritual Emotional Freedom Technique) In Assist of Hypertension Treatment Program at Elderly - Indra Ruswadi; Ike Puspitaningrum; Niken Wulan Hasthi Murti (The International Science of Health Journal, 2023)
Hypertension is a silent disease that causes of unexpected death for sufferers. They do not know that they have hypertension before checking their blood pressure. Various methods can be used to manage hypertension is using SEFT (Spiritual Emotional Freedom Technique). SEFT is a combination of spirituality such as prayer, sincerity, surrender with psychology energy. The purpose of this research is to determine the level of effectiveness of SEFT complementary therapy in assist of hypertension treatment programs at elderly. Method: The method of this research is a quantitative using Quasy Experiment Approach with pre-post test control group design. The statistic analyzed descriptive and statistical test using Wilcoxon Signed Ranks Test. Results: The results of the statistical test on the blood pressure of the experimental group showed that there was a significant difference in the systolic and diastolic blood pressure of hypertension sufferers (experimental group), before and after the SEFT complementary and the result of the statistical test on the blood pressure of the control group concluded that there was no significant difference on the blood pressure of hypertension sufferers without being given SEFT complementary therapy at the beginning of the treatment and at the end of the treatment. The finding of this study is the use of SEFT therapy that given together with hypertension therapy program can help to control the blood pressure of hypertension sufferers.